1996
DOI: 10.1209/epl/i1996-00563-6
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of single-atom resonance fluorescence

Abstract: The emission spectrum of the bichromatically excited resonance fluorescence of a single atomic particle, i.e. of a permanently trapped and cooled Ba + ion has been recorded. It shows up to five peaks, two of them partially resolved, in agreement with fluorescence spectra of three-level atoms calculated from sets of parameters separately measured from recorded excitation spectra of the integrated fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Because of the lower saturation parameter for a nonzero detuning, the elastic part can no longer be neglected in our analysis. We thus include equation (4) in the computation of the total spectrum given by (11) where, as before, the finite size of the laser waist and the temperature are accounted for. In particular, the temperature not only broadens the carrier of the inelastic spectrum, but also turns the homogeneous elastic component into a Doppler-broadened Gaussian peak.…”
Section: Off-resonance Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the lower saturation parameter for a nonzero detuning, the elastic part can no longer be neglected in our analysis. We thus include equation (4) in the computation of the total spectrum given by (11) where, as before, the finite size of the laser waist and the temperature are accounted for. In particular, the temperature not only broadens the carrier of the inelastic spectrum, but also turns the homogeneous elastic component into a Doppler-broadened Gaussian peak.…”
Section: Off-resonance Spectrummentioning
confidence: 99%
“…This led to a first quantitative agreement with theory in 1977 [9], despite the presence of unaccounted effects such as the inhomogeneous broadening due to the nonuniformity of the laser field. Since then, the Mollow triplet has been observed in many different systems: ions [11], single molecules [12], or quantum dots [4,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For low excitation intensities the fluorescence spectrum of a two-level atom exhibits an elastic peak centered at the incident laser frequency ω L , while for higher intensities an inelastic component becomes dominant, with contributions at the frequencies ω L and ω L ± Ω 0 [36], where Ω 0 denotes the effective Rabi frequency. This so-called "Mollow triplet" arises from the dynamical Stark splitting of the two-level transition and has been observed in a number of experiments, using low-density atomic beams [37,38,39] or a single trapped and laser-cooled Ba + ion [40]. Surprisingly, there are only few experimental investigations of the elastic scattering process with a frequency distribution equal to the exciting laser.…”
Section: Spectral Propertiesmentioning
confidence: 99%
“…A review of related theoretical and experimental work is found in references [45,46]. Dark resonances in ionic spectra are reported, for example, using trapped Ba + ions [47][48][49], with Ca + [50][51][52][53], with Sr + [54,55], and Yb + [56], and have been used for cooling of Ba + [57] and Ca + [58].…”
Section: Laser Cooling Using Electromagnetically Induced Transparmentioning
confidence: 99%